PENGARUH KESELAMATAN KESEHATAN KERJA, PENGAWASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. BALI OCEAN MAGIC - I Nyoman Rahayu Putra; I Made Hedy Wartana (Journal Research of Management, 2022)
that can improve performance. And can make a full contribution in helping companies to improve service quality. This study aims to examine work safety, work supervision, and work discipline of employees who conduct case studies on employees at PT. Bali Ocean Magic (Waterbom) Kuta, Bali. determine the sample using certain considerations. The number of respondents used in this study were 65 people. The results of the study stated that Health and Safety had a positive effect on employee performance with a value of = 0.022 < (0.05). This shows that H1 is accepted and H0 is rejected. Work supervision has a positive effect on employee performance with a value of = 0.020 < (0.05). This shows that H2 is accepted and H0 is rejected. The results of the t-statistical test also state that Work Supervision (X2) has a partial effect on Employee Performance (Y) at PT. Bali Ocean Magic (Waterbom) Kuta. Work discipline has a positive effect on employee performance with a value of = 0.020 < (0.05). This shows that H3 is accepted and H0 is rejected. The results of the t-statistical test also state that Work Discipline (X3) has a partial effect on Employee Performance (Y) at PT. Bali Ocean Magic (Waterbom) Kuta. The analytical technique used in this research is descriptive analysis using SPSS 22.00 application software. In this study, respondents' answers were classified in the form of answers using an interval scale with the Likert scale method.